Legal Protection for Abusers as Self-Victimizing Victims in Countermeasures to Narcotics Crimes - Vera Desti Puspitasari; Muhammad Azil Maskur (Law Research Review Quarterly, 2026)
Narcotics abuse is a social and legal problem that has various serious impacts in Indonesia. Not only individuals who consume them impact, but also have a wide impact on the people around them and the country's legal system. Therefore, the handling of narcotics abusers must be carried out comprehensively. Narcotics abusers are often positioned as mere perpetrators of crimes, even though they are also victims of psychological and physical dependence. The case described above creates a special concept known as self-victimizing victims, who are individuals who are victims of their own criminal acts. In Law Number 35 of 2009 concerning narcotics, there are regulations regarding criminal penalties for narcotics abusers, however law enforcement is still predominantly repressive. This article aims to knowing and understanding the concept of self-victimizing victims in drug abusers as an effort to overcome narcotics crimes, and to describe and provide policy recommendations regarding legal protection for narcotics abusers as self-victimizing victims in order to improve the prevention of narcotics crimes that are more humane and proportional. Therefore, the problem formulation emerged: 1.) How is the concept of self-victimizing victims in narcotics abusers as countermeasures to narcotics crimes? And, 2.) How is the policy recommendations legal protection for narcotics abusers as self-victimizing victims to overcome narcotics crimes?. This study uses a normative juridical research method with a qualitatively approach. In this study, it was found that legal protection for drug abusers as self-victimizing victims requires policy reform through a double track system approach, repressive and rehabilitative punishment.